MEDICAL TERMINATION OF PREGNANCY IN THE CATS OF 30-35 DAYS OF GESTATION: EVALUATING THE EFFICACY OF CLOPROSTENOL AND CABERGOLINE - B.R. Baby Roshini; J. Umamageswari; G. Vijayakumar; S. Subapriya; K. Ravikumar; R. Sureshkumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Eighteen queen cats with a history of mis-mating were confirmed pregnant by ultrasound examination and were divided into three groups of six cats each; Group I: Normal pregnancy cats, group II: Cats treated with cloprostenol alone and Group III: Cats that underwent treatment with cloprostenol and cabergoline for medical termination of pregnancy (MTP). Haematobiochemical and ultrasonographic aspects associated with MTP as well as the efficacy of cloprostenol administration alone and its combination with cabergoline in inducing MTP were studied. Ultrasonographic evaluation showed a significant increase in mean heart rate and a decrease in mean gestational sac diameter (p ≤ 0.01) values after 72 hours of initiation of the MTP treatment. Haematological parameters showed a significant reduction in RBC and PCV values; however, there was a significant increase in WBC and neutrophil values on post-hours treatment. Hence, the use of combined therapy (cloprostenol and cabergoline) can be considered a more effective protocol for MTP than single-drug therapy (cloprostenol) from 30- 35 days of pregnancy in cats.